2007
DOI: 10.1080/08860220601095785
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Sodium Dialysate in Chronic Hemodialysis Patients: An Echocardiographic Study

Abstract: A reduction of the dialysate sodium concentration based on the predialysis sodium levels of the patients could reduce the systolic BP and decrease the volume load on the heart as assessed by echocardiography. Within this short period, postdialysis diastolic BP could not be lowered. The effect of this approach should be studied in broad and lengthy series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 16 publications
3
34
0
Order By: Relevance
“…This is consistent with previous trials in thrice weekly conventional haemodialysis patients [27][28][29][30]. However, there was no difference in intradialytic change in systolic, diastolic or mean blood pressure between HIGHDialSOD and LOWDialSOD study periods.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is consistent with previous trials in thrice weekly conventional haemodialysis patients [27][28][29][30]. However, there was no difference in intradialytic change in systolic, diastolic or mean blood pressure between HIGHDialSOD and LOWDialSOD study periods.…”
Section: Discussionsupporting
confidence: 81%
“…In conventional thrice weekly haemodialysis, positive sodium balance is associated with IDWG, hypertension, left ventricular hypertrophy, cardiovascular morbidity and perhaps mortality [5,[26][27][28][29][30]36,37] although the relationship with mortality remains controversial [38]. The clinical effects of frequent or prolonged exposure to sodium concentrations have not been prospectively evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Sayarlioglu et al (46) used the predialysis sodium of 18 patients as a reference to set the dialysate sodium concentration. For those patients who had pre-HD sodium less than 137 mEq/L, the dialysate sodium was modified to 135 mEq/L, and for those with pre-HD sodium over 137 mEq/L, the dialysate sodium was modified to 137 mEq/L.…”
Section: Dialysate Sodium Individualization Decreases Thirst Idwg Amentioning
confidence: 99%
“…In contrast, diffusive sodium loss can lead to intradialytic symptoms, such as hypotension and muscle cramps, if the sodium concentration is lower in the dialysate than in serum (negative sodium gradient). Previous studies have reported that reduction in dialysate sodium based on pre-HD plasma sodium levels improves thirst, interdialytic weight gain (IDWG), hypertension and intradialytic hypotension (Murisasco et al 1985;de Paula et al 2004;Sayarlioglu et al 2007). However, we could not find any studies on individualized dialysate sodium prescriptions for patients who have serum sodium concentrations higher than typical dialysate sodium concentrations.…”
Section: Introductionmentioning
confidence: 99%